OCT-Diagnostik beim Glaukom: Tipps & Tricks - Mardin, Christian (Klinische Monatsblätter für Augenheilkunde, 2020)
High-resolution optical coherence tomography (OCT) with spectral-domain or swept-source techniques has become a mainstay in glaucoma and progression diagnosis. Imaging and morphometry of ganglion cell (GCL) and retinal nerve fiber (RNF) layer thickness and Bruch's membrane based minimum neuroretinal rim width (BMO-MRW) measurement allow the detection of pathologic changes. Graphic display of these measurements facilitate a comparison with normative data. False positive (red disease) and false negative (green disease) results represent pitfalls in OCT diagnosis. Pathologies of the posterior pole either caused by glaucoma or non-glaucoma associated changes of optic disc and retina play an important role. Epiretinal gliosis, age related macular degeneration and cystoid retinal changes cause measuring artefacts. A careful inspection of OCT B-scans is mandatory to detect these changes. Highly myopic eyes, underrepresented in normative databases cause changes resembling glaucoma and challenge the OCT glaucoma diagnosis. Neurological diseases present an important differential diagnosis when atrophy of neuroretinal tissue and ganglion cells occur. The location of the atrophy and the relationship of GCL, RNF and BMO-MRW changes may help in differential diagnosis. Sensory tests and imaging of the brain are mandatory in these cases. Drusen and disc edema cause thickening of BMO-MRW and may be followed by loss of RNF and GCL. Again a close observation of OCT B-scans and fundus may help to find the correct diagnosis. Good image quality, knowledge of OCT pathologies and technique of OCT imaging may help to avoid pitfalls in OCT glaucoma diagnosis.
CRIS-Team Scopus Importer:2020-05-22
Keywords: BMO-MRW; differential diagnosis; glaucoma; OCT; RNF